2022
DOI: 10.1186/s12906-022-03581-6
|View full text |Cite
|
Sign up to set email alerts
|

Interest and need for continuing medical education in pediatric complementary and integrative medicine: a cross-sectional survey from Switzerland

Abstract: Background Pediatric integrative medicine, combining conventional and complementary medical approaches for children and adolescents, is an integral part of the health care system in Switzerland. However, there is still a lack of complementary and integrative medicine topics in training and continuing educational programs. For the first time on a national level, the 2021 annual conference of the Swiss Society of Pediatrics was entirely dedicated to the topic of integrative medicine. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“… 52 A study from Switzerland confirmed increasing interest in integrative medicine among pediatricians, supporting the need for pre-and postgraduate pediatric training related to CAM and integrative oncology. 53 Pediatric healthcare professionals are trained to guide children through difficult treatment processes and handle emotions that arise. Healthcare providers without training may impose an indirect risk on children and their families.…”
Section: Discussionmentioning
confidence: 99%
“… 52 A study from Switzerland confirmed increasing interest in integrative medicine among pediatricians, supporting the need for pre-and postgraduate pediatric training related to CAM and integrative oncology. 53 Pediatric healthcare professionals are trained to guide children through difficult treatment processes and handle emotions that arise. Healthcare providers without training may impose an indirect risk on children and their families.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a small group of patients may come with preexisting behavioral problems, such as hyperactivity attention disorders, which are treated with psychostimulants and other compounds [ 34 , 35 , 36 ]. As for the other psychotropic medications, pediatric oncologists need to pay attention when selecting the appropriate therapy, especially in relation to possible interactions with the cancer treatment proposed, avoiding that the combination of these treatments creates SABEPs [ 37 ].…”
Section: Clinical Questionsmentioning
confidence: 99%